Occupational Rehabilitation Is Associated With Improvements in Cognitive Functioning - Johansen, Thomas; Jensen, Chris; Eriksen, Hege R.; Lyby, Peter S.; Dittrich, Winand H.; Holsen, Inge N.; Jakobsen, Hanne; Øyeflaten, Irene (Frontiers in Psychology, 2019)
Introduction: Occupational rehabilitation may be offered to workers on long-term sick leave who often report problems with cognitive functioning, anxiety, depression, pain and reduced work ability. The empirical knowledge is sparce on how occupational rehabilitation may influence cognitive functioning and patients have not previously been subjected to comprehensive objective testing. The main aim of this study was to assess possible changes in cognitive functioning such as memory, attention and executive function among patients in occupational rehabilitation and the degree to which these possible changes were associated with changes in work ability, return-to-work self-efficacy, anxiety, depression and pain. Methods: A pre-post controlled design was applied to investigate changes in cognitive functioning and work and health measures in a large sample of 280 sick-listed workers referred to occupational rehabilitation. The control group consisted of 70 healthy workers. Computerised cognitive and emotional tests using the CANTAB battery in addition to validated work and health questionnaires were administered at pretest and posttest to both groups. Results: Compared to the control group, the rehabilitation group had greater gains from pretest to posttest in focused and sustained attention, as well as greater improvements in work ability and reduction in subjective health complaints, helplessness, pain, pain related to work, anxiety and depression. In the rehabilitation group, improvement in focused and sustained attention was associated with improvements in return-to-work self-efficacy, work ability as well as a reduction in subjective health complaints. Conclusions: The sick-listed workers improved in focused and sustained attention and work and health measures after participating in occupational rehabilitation. This study is one of the first to systematically investigate changes in cognitive functioning during occupational rehabilitation. Clinical practice should benefit from increased knowledge about cognitive functioning and the fact that improvements were evident in focused and sustained attention. Memory, executive functioning or emotion recognition remained unchanged. The results can be used as motivation to tailor specific interventions to gain further improvements in all cognitive functions.